Visual Design Face Painting: Language Expressions Stylized for Wayang Punakawan - Andreas James Darmawan (Bina Nusantara University, 2017)
On this research, the author focused on the scope of Punakawan face painting that expected to become a starting point from the first step in making the visual standardization proposals, which the visual variety of face painting Punakawan was not consistent yet. The research objective was to become one of the methods to re-popularizing by building a visual consistency in Punakawan face painting so that it became more modern and simple without losing the original characteristics of it. The method was performed in the visual design, from visual references research, visual analysis and matching with the characteristics of each character in Punakawan, visual sketching, and computerization process, up to become final visual artwork. The benefits of the research were to be a next visual research comparison, as well as a contribution in the form of visual work; face painting Wayang Punakawan in the further development of the creative economy entered a new era. This research finds that visually, it is the necessary continuation of the design, such as attribute, proportion, gestures, and other visual elements in Punakawan face painting and it is good for Punakawan studies and other Indonesian wayang figures.